2015
DOI: 10.4037/ccn2015937
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Nursing Checklist to Facilitate Implementation of Therapeutic Hypothermia After Cardiac Arrest

Abstract: I n the United States, 359 400 people experience an out-of-hospital cardiac arrest each year, and less than 9.5% of those people survive. 1 Out-of-hospital cardiac arrest continues to be associated with high mortality, and among those patients who do survive the initial cardiac arrest, two-thirds die as a result of neurological injury.2 Postresuscitation care is increasingly recognized as an integral component in improving the quality of survival and neurological outcomes. Although advances have been made in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Shivering must be identified and quantified using consistent language for TTM to be safely and effectively incorporated into patient care. Despite the subjective limitations of the BSAS, it provides common language and has enabled research investigation and bedside evaluation of pharmacologic and non-pharmacologic patient shivering interventions [70][71][72][73][74][75]. More research is needed to develop objective measurement tools.…”
Section: Recommendationsmentioning
confidence: 99%
“…Shivering must be identified and quantified using consistent language for TTM to be safely and effectively incorporated into patient care. Despite the subjective limitations of the BSAS, it provides common language and has enabled research investigation and bedside evaluation of pharmacologic and non-pharmacologic patient shivering interventions [70][71][72][73][74][75]. More research is needed to develop objective measurement tools.…”
Section: Recommendationsmentioning
confidence: 99%
“…Checklists have already been successfully implemented in a variety of settings in health care. The implementation of a checklist was found to increase the rate of a successful and timely implementation of a therapeutic hypothermia protocol in one ICU (Avery et al, 2015). Another meta-analysis concluded that the use of a surgical safety checklist can improve patient outcomes, team communication, and safety (Lyons & Popejoy, 2014).…”
Section: Available Knowledgementioning
confidence: 99%